PHARMACEUTICAL TERMINOLOGY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Pharmaceutical terminology is a specialized language used in the field of pharmacy and healthcare to describe various aspects of medicines, their development, and their use. This language is crucial for healthcare professionals, pharmacists, researchers, and anyone involved in the pharmaceutical industry